Can grapheme-color synesthesia be induced by hypnosis? - Anderson, Hazel P.; Seth, Anil K.; Dienes, Zoltan; Ward, Jamie (Frontiers in Human Neuroscience, 2014)
Grapheme-colour synaesthesia is a perceptual experience where graphemes, letters or words evoke a specific colour, which are experienced either as spatially coincident with the grapheme inducer (projector sub-type) or elsewhere, perhaps without a definite spatial location (associator sub-type). Here, we address the question of whether synaesthesia can be rapidly produced using a hypnotic colour suggestion to examine the possibility of ‘hypnotic synaesthesia’, i.e. subjectively experienced colour hallucinations similar to those experienced by projector synaesthetes. We assess the efficacy of this intervention using an “embedded figures” test, in which participants are required to detect a shape (e.g., a square) composed of local graphemic elements. For grapheme-colour synaesthetes, better performance on the task has been linked to a higher proportion of graphemes perceived as coloured. We found no performance benefits on this test when using a hypnotic suggestion, as compared to a no-suggestion control condition. The same result was found when participants were separated according to the degree to which they were susceptible to the suggestion (number of coloured trials perceived). However, we found a relationship between accuracy and subjective reports of colour in those participants who reported a large proportion of coloured trials: trials in which the embedded figure was accurately recognised (relative to trials in which it was not) were associated with reports of more intense colours occupying a greater spatial extent. Collectively, this implies that hypnotic colour was only perceived after shape detection rather than aiding in shape detection via colour-based perceptual grouping. The results suggest that hypnotically induced colours are not directly comparable to synaesthetic ones.